Factores que influyen a la desnutrición infantil en los niños menores de 5 años en el área de pediatría del Hospital Martin Icaza de la Ciudad de Babahoyo provincia Los Ríos, del periodo mayo - agosto 2024. - Atiencia Jacome, Johana Lisbeth (2024)
Childhood malnutrition remains a significant problem in many developing countries, including Ecuador. This study investigates the factors that influence malnutrition in children under 5 years of age in the pediatric area of the Martín Icaza Hospital, located in the city of Babahoyo, province of Los Ríos, during the period from May to August 2024. The main objective is to determine the factors that influence childhood malnutrition in children under 5 years of age in the pediatric area of the Martin Icaza Hospital in the city of Babahoyo, province of Los Ríos, during the period May - August 2024. The study used a quantitative approach to measure and analyze the prevalence and factors associated with malnutrition in the child population of the region. Field research was carried out using structured surveys and review of medical records to collect data on socioeconomic factors, feeding practices, access to health services, and other determinants related to child nutrition.